2020
DOI: 10.3390/nu12040920
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis—An Easy Tool for Quantifying Body Composition in Infancy?

Abstract: There has been increasing interest in understanding body composition in early life and factors that may influence its evolution. While several technologies exist to measure body composition in infancy, the equipment is typically large, and thus not readily portable, is expensive, and requires a qualified operator. Bioelectrical impedance analysis shows promise as an inexpensive, portable, and easy to use tool. Despite the technique being widely used to assess body composition for over 35 years, it has been sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…It appears that TANITA and BIACORPUS, which are non-invasive and easily applied devices, could be appropriate to measure body composition in young patients with obesity. Previous studies found that bioelectrical impedance-based methods may be accurate enough to provide reliable measurements [ 30 , 31 ], and in other studies a more limited reliability was defined [ 26 , 32 , 33 ], except for individuals with obesity, but not for patients with morbid obesity [ 34 ], or a clear need of optimization for young patients with obesity [ 35 ], highlighting the need to be cautious when applying it. It thus appears important that future research conducts a thorough comparison of TANITA and BIACORPUS with DXA.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that TANITA and BIACORPUS, which are non-invasive and easily applied devices, could be appropriate to measure body composition in young patients with obesity. Previous studies found that bioelectrical impedance-based methods may be accurate enough to provide reliable measurements [ 30 , 31 ], and in other studies a more limited reliability was defined [ 26 , 32 , 33 ], except for individuals with obesity, but not for patients with morbid obesity [ 34 ], or a clear need of optimization for young patients with obesity [ 35 ], highlighting the need to be cautious when applying it. It thus appears important that future research conducts a thorough comparison of TANITA and BIACORPUS with DXA.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that TANITA could be appropriate to measure body composition in young obese patients. However, although previous studies found that bioelectrical impedance-based methods may be accurate enough to provide reliable measurements [25,26], in other studies a more limited reliability was de ned [21,27,28], except for obese, but not morbid obese patients [29], or a clear need of optimization for young obese patients [30], highlighting the need to be cautious when applying it.…”
Section: Discussionmentioning
confidence: 92%
“…Bioelectrical impedance analysis (BIA) is used to assess the body composition and hydration status. This technique represents a non-invasive, reliable, and fast clinical approach, which is well tolerated and widely accepted by patients [4][5][6][7][8][9][10][11][12]. In the study of Bai et al, an excellent test repeatability throughout pregnancy has been demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…BIA devices may vary depending on the electrode characteristics (number, type and location), the frequency of electric current (single or multiple frequencies), and the position of the body during measurements [16]. This standardised method works by measuring the electrical resistance of the body tissues at different frequencies in relation to the body fluid volume (Figure 2) [12,17]. The electrical conductivity is proportional to the amount of water or electrolytes, which allows BIA to quantify intracellular (ICW) and extracellular water (ECW) as well as the fat and muscle mass.…”
Section: Introductionmentioning
confidence: 99%